Discovery and characterization of cyclotides, plant-based peptides from Viola dalatensis Gadnep - Son, Pham Hoa; Tam, Tran Thi Thanh; Yen, Pham Nguyen Dong; Binh, Le Xuan; Thinh, Nguyen Hung; Cuong, Truong Quang; Dung, Le Tien; Tien, Dang Thuy (Vietnam Journal of Biotechnology, 2024)
Cyclotides demonstrate remarkable stability due to their unique characteristic - the cyclic cystine knot motif. Cyclotides exhibit a wide range of biological activities. This study aims to explore the presence of cyclotides in Viola dalatensis Gadnep, a plant indigenous to Vietnam, through the utilization of LC-MS and LC-MS/MS techniques. We conducted a comprehensive analysis of three extraction methods: 50% acetonitrile with 1% formic acid, 70% ethanol, and 50% methanol. The initial method is extremely efficient for cyclotide extraction when utilizing LC-MS analysis. An ammonium sulfate salt concentration of 30% is used to enhance the cyclotide content and optimize the RP-HPLC purification procedure. The precipitates demonstrate a notable advantage in terms of antibacterial properties compared to the extracts, particularly when the antibacterial concentration is decreased by a factor of four in comparison to the extracts. The combination of cyclotides demonstrated potent antimicrobial activity against Bacillus subtilis and Pseudomonas aeruginosa. The impact was most noticeable when the concentration of the cyclotide mixture was ten times lower than the precipitates. The inhibition zones for these bacteria measured 17.17 ± 2.24 mm and 20.23 ± 0.84 mm, respectively. The identification of the primary structure of nine cyclotides through LC-MS/MS analysis was successfully achieved.